Daya Tarik Kawasan Tepian Sungai Musi Sebagai Destinasi Wisata Kota Palembang - Selly Novitasari; Myrza Rahmanita (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Palembang City in South Sumatra Province has various tourism potentials, including historical, cultural, religious and natural tourism. As well as the Musi waterfront area has potential that can be developed into Palembang city destinations, given its strategic position and become a place of life where urban culture grows on the waterfront. The purpose this research is to analyze potential of tourist attractions in the Musi River waterfront area. The method used is a qualitative approach with a descriptive research type. The data collection technique this writing is through literature study by collecting data from literature, about description of tourist destinations in the Musi waterfront area. The results show along the Musi waterfront area there are many potentials of tourist attractionsthat hold historical and cultural values. Tourism potential that will be found along the banks of the Musi River starts from Fort Kuto Besak (BKB), Ampera Bridge, Pasar 16 Ilir, Sultan Mahmud Badaruddin II Museum, Monument to the People's Struggle Museum, Great Mosque, Al-Munawar Arab Village, Kemaro Island, Kampung Kapitan, and Rumah Baba Boentjit both those that have been developed and the potential that can be further developed so that they can increase the number of tourist visits in Palembang City.